2019
DOI: 10.4236/jep.2019.1010074
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Quantification and <i>In-Vitro</i> Genotoxicity of Major Polyaromatic Hydrocarbons Produced by Sugarcane Fly Ash Emitted from Sugarmill

Abstract: Sugarcane burning during harvest and non-harvest season emits various pollutants like volatile organic compounds (VOCs), alkanes, and PAHs (Polyaromatic hydrocarbons) in the surrounding environment. Among these pollutants, PAHs are of uttermost concern due to their high level of toxicity. Burning of sugarcane bagase in sugar mill results in the production of fly ash. Fly ash is produced as a result of sugarcane bagasse burning in sugar mills. In present study, fly ash that comes out from the sugar mill chimney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This shows that contamination depends on time of exposure to the source of PAHs. Naphthalene has been indicated to be a very harmful compound consequent upon its cytotoxic effects [17]. The study revealed 94% and 95 % contamination of the PAH from smoke in the smoked semi-dried and smoked dried fish which is a pointer to the fact that naphthalene contaminated the smoked fish highly.…”
Section: Resultsmentioning
confidence: 93%
“…This shows that contamination depends on time of exposure to the source of PAHs. Naphthalene has been indicated to be a very harmful compound consequent upon its cytotoxic effects [17]. The study revealed 94% and 95 % contamination of the PAH from smoke in the smoked semi-dried and smoked dried fish which is a pointer to the fact that naphthalene contaminated the smoked fish highly.…”
Section: Resultsmentioning
confidence: 93%